Discovery of myricetin as an inhibitor against Streptococcus mutans and an anti-adhesion approach to biofilm formation - Ping Hu (International Journal of Medical Microbiology, 2021)
Streptococcus mutans (S. mutans) are cariogenic microorganisms. Sortase A (SrtA) is a transpeptidase that attaches Pac to the cell surface. The biofilm formation of S. mutans is promoted by SrtA regulated Pac. Myricetin (Myr) has a variety of pharmacological properties, including inhibiting SrtA activity of Staphylococcus aureus. The purpose of this research was to investigate the inhibitory effect of Myr on SrtA of S. mutans and its subsequent influence on the biofilm formation. Here, Myr was discovered as a potent inhibitor of S. mutans SrtA, with an IC50 of 48.66 ± 1.48 μM, which was lower than the minimum inhibitory concentration (MIC) of 512 ug/mL. Additionally, immunoblot and biofilm assays demonstrated that Myr at a sub-MIC level could reduce adhesion and biofilm formation of S. mutans. The reduction of biofilm was possibly caused by the decreased amount of Pac on the cells’ surface by releasing Pac into the medium via inhibiting SrtA activity. Molecular dynamics simulations and mutagenesis assays suggested that Met123, Ile191, and Arg213 of SrtA were pivotal for the interaction of SrtA and Myr. Our findings indicate that Myr is a promising candidate for the control of dental caries by modulating Pac-involved adhesive mechanisms without developing drug resistance to S.mutans.